2019
DOI: 10.3390/rs11111359
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Vegetation Latent Heat Flux over Three Forest Sites in ChinaFLUX using Satellite Microwave Vegetation Water Content Index

Abstract: Latent heat flux (LE) and the corresponding water vapor lost from the Earth's surface to the atmosphere, which is called Evapotranspiration (ET), is one of the key processes in the water cycle and energy balance of the global climate system. Satellite remote sensing is the only feasible technique to estimate LE over a large-scale region. While most of the previous satellite LE methods are based on the optical vegetation index (VI), here we propose a microwave-VI (EDVI) based LE algorithm which can work for bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…A series of studies in midlatitude forest and Amazonian rainforest have confirmed its validity (Li & Min, 2013; Min et al, 2010; Min & Lin, 2006b). Recently, it has also been used to estimate the evapotranspiration rates at some forest sites in East Asia (Wang, Li, Min, Fu, et al, 2019, Wang, Li, Min, Zhang, et al, 2019). However, its spatiotemporal features over large‐scale complex land cover mixed with vegetation (forest, crops, and grass), bare soil, and open water were not clear yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of studies in midlatitude forest and Amazonian rainforest have confirmed its validity (Li & Min, 2013; Min et al, 2010; Min & Lin, 2006b). Recently, it has also been used to estimate the evapotranspiration rates at some forest sites in East Asia (Wang, Li, Min, Fu, et al, 2019, Wang, Li, Min, Zhang, et al, 2019). However, its spatiotemporal features over large‐scale complex land cover mixed with vegetation (forest, crops, and grass), bare soil, and open water were not clear yet.…”
Section: Discussionmentioning
confidence: 99%
“…The temporal correlation coefficient between satellite observed EDVI and ground measured evapotranspiration fraction can be as high as 0.79 (Min & Lin, 2006a). Using EDVI as dynamic variable in the vegetation conductivity and environmental stress function, satellite algorithms for retrieving ET rate have been developed for Harvard forest site (Li et al, 2009) and East Asia forest sites (Wang, Li, Min, Fu, et al, 2019; Wang, Li, Min, Zhang, et al, 2019). Instantaneous satellite retrieved ET under all sky conditions are found to have a bias of 16.5 W/m 2 (13.7%) and a root mean square error of 63.6 W/m 2 (52.5%) over East Asia forest sites.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of water vapor exchange and carbon exchange processes between the land and the atmosphere strongly depends on the characteristics of the vegetation water content. The MLSE results in this study were successfully used in the retrieval of vegetation water content [70], the estimation of water vapor evapotranspiration rate in mid-latitude forests [15,16,71], and the volatile organic gas emissions [17]. The influence of clouds on the evapotranspiration process has also been studied using MLSE-based products [72].…”
Section: Potential Applicationsmentioning
confidence: 92%
“…First, MLSE largely determines the background brightness temperature in the over-land emission-based retrievals of precipitation [8][9][10]. Second, MLSE has wide applications in monitoring/estimating surface properties and processes, including but not limited to soil moisture, surface evapotranspiration, and forest carbon uptake [11][12][13][14][15][16][17], assessment of wildfire risk [18,19], determination of vegetation physiology activity (respiration and photosynthesis), and the estimation of gross primary production and above ground biomass [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The key hydrologic variables such as evapotranspiration (ET) and precipitation were derived and evaluated at varying spatial and temporal resolutions. Wang et al [4] proposed a latent heat flux (LE) algorithm based on a novel microwave vegetation index (EDVI) instead of the optical vegetation index that was commonly used in previous studies. This algorithm was driven by multiple-sensor satellite products of vegetation water content index, solar radiation, and cloud properties, with some aid from a reanalysis dataset.…”
mentioning
confidence: 99%